تأثير بعض المستخلصات النباتية على نمو فطر ochraceus Aspergillus (Albayan Scientific Journal, 2023)
: In recent years, interest in the use of medicinal herbs has increased in several countries, especially developing countries such as Libya. As the importance of the study is reflected in the possibility of identifying the effectiveness of plant extracts in combating toxin-producing fungal pathogens, we aimed to evaluate the efficiency of some aquatic plant extracts on the growth of Aspergillus ochraceus. Which was isolated from some dried fruits collected from the markets of the city of Misurata after evaluating the toxicity of the isolated fungi, most of which were the two masters of the study, The results of a study of the inhibitory effect of hot aqueous plant extracts of Zizyphus vulgaris leaf powder, Thymus vulgaris and Nigella sativa extract on the growth of A. ochraceus showed the highest inhibitory effect of the aqueous extract of thyme at 50% with a slight inhibitory effect of Sidr aqueous extract at percentage. 12.5% ​​and the inhibitory effect was small for the aqueous extract of Nigella sativa by 7.5%.). Therefore, it is necessary to spread awareness among consumers of the danger of fungal contamination and mycotoxins for food, in addition to following strict requirements in the good storage of dried fruits.
Keywords: dried fruits; Aspergillus ochraceus; mycotoxins, plant extracts